Comparison of immediate and short‐term outcomes of cricoarytenoid and thyroarytenoid lateralization in dogs with idiopathic laryngeal paralysis. Issue 3 (2nd February 2022) - Drudi, Dario; Lisi, Marta L. P.; Sommaruga, Paolo; Chiti, Lavinia E.; Massari, Federico
Abstract: Objective: To compare the immediate and short‐term outcomes of thyroarytenoid lateralization (TAL) and cricoarytenoid lateralization (CAL) for the treatment of canine laryngeal paralysis in dogs. Study design: A prospective, clinical trial. Animals: Fourteen client‐owned dogs referred to our hospital because of bilateral laryngeal paralysis. Methods: Dogs with confirmed laryngeal paralysis were randomly assigned to the CAL or TAL group. Video images of the rima glottidis obtained preoperatively, immediately postoperatively (t0), and 15 days postoperatively (t1) were digitized. The rima glottidis area was measured using image‐analysis software. An increase in the rima glottidis area was expressed as a percentage of the preoperative area. Results: The rima glottidis area increased by a mean of 152% at t0 and 127% at t1 for the TAL group and 205% at t0 and 199% at t1 for the CAL group compared with preoperative values. The increase in the rima glottidis area differed ( P < .05) between the 2 groups at all postoperative time points. A reduction of the area occurred at t1 in both groups. There was no difference between t0 and t1 ( P > .05) in the CAL group but there was a large difference ( P < .05) in the TAL group. Conclusion: Cricoarytenoid lateralization and TAL were both effective for surgical abduction of the arytenoid cartilage. Although a reduction ( P < .05) in the rima glottidis area occurred in the TAL group at t1, we observed no associated clinical signs. Clinical significance: Cricoarytenoid lateralization and TAL result in good short‐term outcomes in dogs with laryngeal paralysis.